Abacavir/lamivudine/dolutegravir single tablet regimen in patients with human immunodeficiency virus and end-stage renal disease on hemodialysis. (February 2019) - Michienzi, Sarah M; Schriever, Christopher A; Badowski, Melissa E
No single-tablet antiretroviral (ARV) regimens (STRs) are approved for patients with human immunodeficiency virus (HIV) and end-stage renal disease (ESRD) on hemodialysis (HD). Based on known pharmacokinetic (PK) properties, abacavir (ABC)/lamivudine (3TC)/dolutegravir (DTG) STR may represent a promising option. This case series presents the safety and efficacy of ABC/3TC/DTG STR in patients with HIV and ESRD on HD. Patients were included if they were HIV-positive, maintained on intermittent HD for ESRD, switched to an ARV regimen containing ABC/3TC/DTG, and had at least one set of virologic data before and after the switch. Average age (±standard deviation) was 59 (±8) years. The majority of patients were cis-gender male and non-Hispanic Black. Only one demonstrated clinically significant resistance at baseline. All were on multiple-tablet regimens prior to the switch. Five patients (83%) achieved undetectable HIV-RNA after the switch while only four patients (46%) were undetectable immediately prior. No decline in immune function was noted. ABC/3TC/DTG STR was well tolerated. Only one patient self-reported an adverse event (nausea), which resolved without drug discontinuation. Based on these data, it appears that ABC/3TC/DTG may be a safe and effective ARV-STR option for patients with HIV and ESRD on HD. A larger trial including a PK analysis is needed to confirm these findings.